ANALISIS DIVERSIFIKASI PENDAPATAN RUMAH TANGGA PETANI - Desy Cahyaning Utami (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
The purpose of this study is to,(1) To analyze the level of diversification of farm household incom e. (2) Analyze the factors that influence the allocation of non -agricultural em ploym ent in the sector. (3) Analyze the factors that affect em ploym ent opportunities in nonagricultural sector.(4) Analyzing the distribution of farm household incom e. (5) Analyzing the impact of policies increased by 10% of land area, the improvem ent of education head of household by 10 %, non-farm incom e increased by 20%, increase in total non-farm time allocation by 20%, and decreased total time allocation of farm by 15%. The results obtained from the study are as follow s: 1. The average household incom e of farmers in Patuk Baran derived from non-farm activities is much higher than from farming activities, am ounting to Rp 7,010,566 for an average farm incom e per year and 13,116,220 for an average incom e of non - farm per year. 2. Factors that significantly affect incom e diversification seen from the allocation of work in the agricultural sector is the head of ho usehold educati on, land area and age of head of household. 3. Factors that affect the em ploym ent opportunities in agriculture, of labor activity in trade is the total time allocation of farm and labor force in the fam ily. To work activities are broad areas of service and age of head of fam ily land. While on work activities rem ittance is head of the fam ily and education on the activities of field workers are working in the fam ily labor force, ed ucation head of household, land area and consum ption. 4. Based on the gini index value of 0.4079 which is still far from one and the Lorenz curve that is close to 45o line and not too convex, then the distribution of incom e in Ham let Patuk Baran evenly. 5. The impact of increased education head of household by 10%, causing an increas e in non-farm incom e, ie incom e trading, services, and labor as well as low er farm receipts. Increased non - farm incom e by 20% impact on increasing trade and services revenue, this policy aims to increase the am ount of em ploy ment or new em ploym ent opportuni ties in rural areas. While the impact of increasing the total time allocation of non -farm non-agricultural sector led to rising incom es Last is the impact of the decline in total time of farming led to declining farm revenues.